El poder de las palabras de los capellanes. El impacto en los colaboradores de la gestión de la espiritualidad laboral (2015)
One way to promote workplace spirituality is through corporate chaplains, who seek to address the spiritual, personal, organizational, and social needs of workers. The aim of this research was to test the dependence between the perceptions of the employees on their spiritual state, among others, and the accompaniment of the chaplain. Mixed methodology and semi-structured interviews were used to determine the dimensions on which the work of the chaplain would impact. Linear regression analysis on a sample of 848 workers of Tyson of Mexico was performed to verify this impact. The results show how the work of chaplains leads to a better perception of workers about their life in the spiritual, psychological, organizational, and family dimensions.